Atomic Layer Deposited RuO2 Diffusion Barrier for Next Generation Ru‐Interconnects. (11th August 2022) - Kim, Youn‐Hye; Kim, Minsu; Kotsugi, Yohei; Cheon, Taehoon; Mohapatra, Debananda; Jang, Yujin; Bae, Jong‐Seong; Hong, Tae Eun; Ramesh, Rahul; An, Ki‐Seok; Kim, Soo‐Hyun
Abstract: Atomic layer deposition (ALD) is a suitable technology for conformally depositing thin films on nanometer‐scale 3D structures. RuO2 is a promising diffusion barrier for Ru interconnects owing to its compatibility with Ru ALD and its remarkable diffusion barrier properties. Herein, a RuO2 diffusion barrier using an ALD process is developed. The highly reactive Ru precursor [tricarbonyl(trimethylenemethane)ruthenium] and improved O2 supply enable RuO2 deposition. The optimal process conditions [pulsing time ratio ( t O2 / t Ru ): 10, process pressure: 1 Torr, temperature: 180 °C] are established for the RuO2 growth. Growth parameters, such as the growth rate (0.56 Å cycle –1 ), nucleation delay (incubation period: 6 cycles), and conformality (step coverage: 100%), are also confirmed on the SiO2 substrate. The structural and electrical properties of the Ru/RuO2 /Si multilayer are investigated to explore the diffusion barrier performance of the ALD‐RuO2 film. The formation of Ru silicide does not occur without the conductivity degradation of the Ru/RuO2 /Si multilayer with an increase in the annealing temperature up to 850 °C, thus demonstrating that interdiffusion of Ru and Si is completely suppressed by a thin (5 nm) ALD‐RuO2 film. Consequently, the practical growth behavior and diffusion barrier performance of RuO2 can serve as a potential diffusion barrier for Ru interconnects. Abstract : The Ru interconnect is a next‐generation technology that can cope with the extreme reduction of the technology node for semiconductor chip fabrication. RuO2 as a diffusion barrier is successfully grown using atomic layer deposition (ALD). A continuous ALD of RuO2 and Ru ALD process realizes the Ru/RuO2 /Si structure to suppress the interdiffusion of Ru and Si at the interface.